PENGARUH AUDIT INTERNAL DAN PENGENDALIAN INTENAL DALAM MENINGKATKAN KINERJA PERUSAHAAN PADA PT. PANEN EMBUN KEMAKMURAN - Milawati, Milawati; Suasri, Eni (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
In the business world, company performance is very important and is the main concern for management. Company performance is a parameter in conducting performance assessments. The main factor in improving performance is the control implemented in the company. Good control will facilitate work activities in the company. Control evaluation can be done by conducting an internal audit of the company. One of the objectives of an audit is to find out whether or not there are abnormal things in a company. This study aims to determine the influence of internal audit, internal control in improving company performance. This research was conducted on PT. Harvest Dew of Prosperity. The type of data in this study is quantitative in the form of data processing from questionnaires using the SPSS version 26 application. The results of the hypothesis test in the form of a partial test show that the internal audit has no effect on improving the company's performance and internal control affect the improvement of the company's performance. The Adjusted R Square value of 0.540 indicates the influence of internal audit and control on improving the company's performance by 54% while the remaining 46% is influenced by other factors.